Effect of Environment Factors on Life Cycle of Forensic Entomology: A Review - Nassreen N. Mzhr 1 : Zaid Raad Abbas2 , Zaid Naji Hassan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pests play an important ecological part in organic matter decomposition. As a natural means of survival,sarcosaprophagous fly usually prefers to locate and consume a food source such as a cadaver as a naturalmeans of survival. Sarcosaprohagous fly larvae are frequently encountered by judicial entomologistsduring post mortem investigations. The most relevant colonizers are the oldest individuals derived fromthe first eggs placed on the body. The stage of the oldest maggots provides the accurate estimate of postmortem interval. Judicial entomology is predictable in numerous countries as a serious tool for forensicinvestigations. Judicial entomology requires extensive information on the local pest population, is subjectto many environmental factors (temperature being one of the principle variables), and they need access tothe bodies. The maggot fly crawling on the dead bodies are broadly considered to be just another disgustingelement of decay and are not collected at the periods of autopsy. This paper reviews several methods of PMIassessment, this procedure comprises the aggregation of convenient information for the growth of the typesof pest at a variation of pertinent temperatures and contemplation of the extra living things and nonlivingthings aspects that can disturb evolving average.